Entrepreneurial Learning Management in Improving the Quality of Graduates - Erwin Sunandar Lubis; Ida Tejawiani (Sekolah Tinggi Ilmu Tarbiyah Madani Yogyakarta, 2025)
The challenges posed by globalization and the high unemployment rate in Indonesia, particularly in West Java, necessitate that vocational high school (SMK) graduates are not only prepared to enter the workforce but also equipped with an entrepreneurial mindset. Consequently, the effective management of entrepreneurship learning is imperative to enhance the quality of graduates. This research is anchored in George R. Terry's management theory, which encompasses the functions of planning, organizing, actuating, and controlling, alongside educational quality theories that emphasize the necessity of competitive, creative, and independent educational outcomes. This study employs a qualitative approach utilizing a case study design at SMK Negeri 1 Cibadak Sukabumi. Data collection techniques included participatory observation, in-depth interviews, and document analysis. The data were analyzed through data reduction, data display, and interactive conclusion drawing. The findings indicate that entrepreneurial learning management at SMK Negeri 1 Cibadak involves: strategic planning of an entrepreneurship-based vision, mission, and programs; organizing through a work structure conducive to innovation; implementing project-based learning and practical business applications; and conducting continuous evaluations of student competencies. Identified obstacles include resource limitations and resistance to change, which are progressively mitigated through teacher competency training and the reinforcement of an entrepreneurial culture. When effectively planned, organized, implemented, and evaluated, entrepreneurship learning management significantly improves the quality of SMK graduates, rendering them both job-ready and entrepreneurial. Strategies focusing on strengthening human resource competencies and fostering collaborations with the business and industrial sectors are critical to successful implementation.